Research Progress of Simulation Methods and Applications for Complex River Network Hydrodynamic Process in the Pearl River Delta - Wang Hangang; Zhang Wenqing; Wang Yu (E3S Web of Conferences)
Developing the Pearl River Delta (PRD) river network hydrodynamic model to simulate the hydrodynamic evolution processes in complex river network areas can effectively mitigate flood disasters and guide the construction of flood control projects. This work introduced the simulation methods of the complex river network hydrodynamic model in PRD, covering aspects such as simulation boundary conditions, model solution methods, and the coupling methods with other models. The applications of PRD river network model in flood pattern simulation, flood forecasting, risk assessment, and digital twin technology were discussed. The future development trends and application prospects of the complex river network model in PRD were analysed. The results indicate that the hydrodynamic simulation methods and applications for the complex river network areas in PRD are relatively mature. However, there are still some urgent issues to be addressed to meet varying engineering needs. This work's discussion on the hydrodynamic simulation methods and applications in PRD river network can serve as a reference for flood disaster prevention in complex river network areas.